Ureteroureterostomy in patients with duplex malformations: does a large diameter of the donor ureter affect the outcome?. Issue 6 (December 2019) - Harms, Mirjam; Haid, Bernhard; Schnabel, Marco J.; Promm, Martin; Roesch, Judith; Oswald, Josef; Rösch, Wolfgang H.
Summary: Introduction: Ureteroureterostomy is a commonly adopted, minimally invasive approach in the management of duplex anomalies requiring diversion, e.g., ectopic upper pole ureters. Objective: The authors hypothesized that a large diameter of the donor ureter could affect the outcome of this procedure. Study design: Forty-two patients from two centers were retrospectively reviewed. To compare patients with small (group 1) vs large donor ureters (group 2), they were split at the median of the sonographically measured diameter at the level of the future anastomosis ( n  = 20 < 1.2 cm, mean 0.71 cm vs n  = 22 ≥ 1.2 cm, mean 1.75 cm; P  < 0.001) Figure. Ureteroureterostomy was performed in an end-to-side fashion with the donor ureter being tapered if required. Results: There was no significant difference in operation time (127 vs 121 min; P  = 0.59) or duration of hospital stay (4.15 vs 4.09 days; P  = 0.89) or number of postoperative complications (3 febrile urinary tract infections [fUTIs] in group 1 and one fUTI in group 2, P  = 0.33). Reoperations during follow-up (1 stump resection and 2 endoscopic vesicoureteral reflux procedures) occurred exclusively in group 1 ( P  = 0.22). The mean pre-operative hydronephrosis grade of the affected moiety was higher in group 2 compared with group 1 (mean 2.73 Society for Fetal Urology classification [SFU] vs 1.65, P  < 0.001). During follow-up, the mean hydronephrosis grade in group 2 improved from 2.73 to 1.36 SFU ( P  = 0.0011). In patients from group 1, the mean hydronephrosis grade remained relatively unchanged, from 1.65 to 1.35 SFU ( P  = 0.4). Discussion: After its first description in 1928, it took almost 40 years for ipsilateral ureteroureterostomy to become a widely adopted technique in the management of duplex malformations, especially for obstructive or ectopic upper pole moieties. Whereas it has been recently shown that the upper pole function does not seem to matter, there are still only narrative reports about the influence of the donor ureter diameter contributing to potential complications such as a de novo hydronephrosis of the receiving ureter with potential damage of the healthy moiety or the persistence of a pre-operatively marked hydronephrosis. While the study data are retrospective, the authors could demonstrate that a ureteral diameter of ≥1.2 cm is not factoring adversely into the occurrence of postoperative complications. Conclusion: A donor ureter diameter ≥1.2 cm in ureteroureterostomy was not associated with a higher complication rate or worse outcome considering further fUTIs or reoperations. The postoperative reduction in hydronephrosis grade was more pronounced in patients with large donor ureters with disappearance of the pre-operative significant difference between the two groups. Figure summary Plot of the ureter size measured at the level of the future anastomosis in the two groups with small (<1.2 cm) or large (≥1.2 cm) sized donor ureter. Figure Extended summary